(untitled) (Palíndromo, 2021)
The following text approaches the relation between contemporary art and other disciplines. It is part of a series of interviews that composed a Master’s thesis research conducted by Suzzana Magalhães de Oliveira and supervised by the professor and researcher Céline Berthoumieux for the University of Lumière – Lyon II, in France, between 2017 and 2018. The dialogue here below, with the visual artist and musician Robert Henke, brings a reflection about how the exchange between the art and other knowledge domains, as the collaboration with other creators and researchers, may be perceived in the thinking and artist’s work. The subjects mentioned in this article allow us to understand better the transdisciplinarity in arts, its difficulties and the lessons it may bring.